UTHM water quality classification based on sub index - Seswoya, R.; Johari, A. H.; Rafek, M. M.K.N (Penerbit UTHM, 2020)
River or stream at their source is unpolluted, but as water flow downstream, the river or lake is receiving point and non-point pollutant source. Ammoniacal nitrogen (NH3- N) and suspended solids (SS) strongly influences the dynamics of the dissolved oxygen in the water. Studies on monitoring this parameter were conducted for a river or lake but limited to the small man-made lake. This study is initiate to determine the changes in water quality of UTHM watershed as the water flows from upstream to downstream. The monitoring of NH3-N and TSS were monitored at two sampling schemes, 1) at the two-week interval and, 2) at a daily basis followed by the determination of the water quality sub-index particularly SIAN and SISS. The results showed that the two lakes in UTHM watershed were classified as polluted. In conclusion, the remedial action should be implemented to improve the water quality to meet the requirements at least to meet the recreational purposes